Characteristics of pyrolytic liquid from automotive paint sludge (APS): article - Jumali, Nur Alimatun Namirah; Abd Rahman, Norazah; Januri, Zakiuddin (2017)
Pyrolytic liquid from automotive paint sludge (APS) has been characterized in this study. APS is categorized as hazardous waste produced from painting department in an automotive industry. It is in slurry form and has been produced in large amount. The cost of treating the waste is high and an alternative treatment method by using microwave assisted pyrolysis (MAP) has been suggested. MAP has been found to be suitable to be used for high moisture content material. Activated carbon as an absorber has been added to the process to assist APS decomposition. Pyrolysis parameters that have been used were microwave power (500W, 600W, 700W) and radiation time (30 min, 40 min, 50 min). It has been found that the products yields are affected by microwave power and radiation time. In this study, liquid product was characterized by measuring its density, determining its calorific value by Bomb Calorimeter, functional groups by using FTIR and GCMS to identify its composition. Both products, solid char and pyrolytic liquid were produce the highest yield at 500W and 30 min. The highest density of the pyrolytic liquid is 939.7 kg/m3 and the highest calorific value of pyrolytic liquid is 38, 274 kJ/kg. The functional group consist in the samples are monoaromatics compounds, heavy oxygenated hydrocarbon, nitrogenated compounds, aliphatic compounds and polycyclic aromatic hydrocarbons. These liquid product had potential for alternative fuel based on the properties obtained in this study and it is potential to replace non-renewable fuel.